Difference in release kinetics of unwashed and washed platelet‐released supernatants from bone substitute materials: the impact of platelet preparation modalities. (6th March 2017) - Knoop, C.; Edelmayer, M.; Janjić, K.; Pensch, M.; Fischer, M. B.; Gruber, R.; Agis, H.
Abstract : Background and objective: In regenerative dentistry, platelet preparations are applied to stimulate bone healing and periodontal regeneration. Here, we pursue a strategy where bone substitutes are used as carriers for platelet‐released supernatants. The mitogenic capacity and release kinetics of loaded bone substitutes were assessed. Material and Methods: Platelet‐released supernatants of washed platelets (washed PRS) and platelet‐released supernatants of unwashed platelets (unwashed PRS) were lyophilized onto the bone substitutes deproteinized bovine bone mineral, hydroxyapatite and β‐tricalcium phosphate. Scanning electron microscopy images were taken. Supernatants of bone substitutes were collected at hours 1, 3, 6, 24, and 48 and medium was replaced. We evaluated the protein content with the bicinchoninic acid assay and the effect on proliferation using bioassays with human periodontal fibroblasts. Release of growth factors from the loaded bone substitutes was measured based on the platelet‐derived growth factor isoform (PDGF‐BB) and thrombin immunoassays. Furthermore, we assessed DNA and RNA content of washed PRS and unwashed PRS. Results: Unwashed PRS showed higher total protein concentrations than washed PRS, while the concentration of PDGF‐BB, thrombin, DNA, RNA and their mitogenic effect was not significantly different. The bone substitute materials adsorbed protein over time but no significant changes in overall appearance was found. Supernatants collected from unwashed PRS‐loaded bone substitute after 1 h induced a potent mitogenic response in periodontal fibroblasts. This pro‐mitogenic capacity of the supernatants decreased over the observation period. Supernatants of washed PRS‐loaded bone substitutes did not induce a substantial mitogenic effect. Levels of PDGF‐BB, thrombin and protein were higher in supernatants of unwashed PRS‐loaded bone substitutes than of washed PRS‐loaded bone substitutes. Conclusion: Bone substitutes loaded with unwashed PRS, but not bone substitutes loaded with washed PRS show continuously declining release kinetics. These data suggest that plasma components in platelet preparations can modify the release kinetics profile.